2015
DOI: 10.1007/978-3-319-18374-9_41
|View full text |Cite
|
Sign up to set email alerts
|

Training and Retraining Motor Functions at Home with the Help of Current Technology for Video Games: Basis for the Project

Abstract: Chronic diseases are an international concern, for their increasing incidence and the strain on individuals and on healthcare systems. In order to enable the health-care system to cope with increasing demands and to avoid strong decrements in subject’s functionality and well-being, a variety of changes for the management of chronic disease care have been advocated by the World Health Organization. The objective of the research is to verify the feasibility and acceptability of a technological solution that allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Real-time video conferences were extensively used in physical telerehabilitation [33][34][35][36]. Giantomassi et al [37] indicated that current video game technologies could be used in physical rehabilitation. Several telerehabilitation programs have been developed using the Microsoft Kinect sensor [38][39][40][41] and the Nintendo Wii board [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time video conferences were extensively used in physical telerehabilitation [33][34][35][36]. Giantomassi et al [37] indicated that current video game technologies could be used in physical rehabilitation. Several telerehabilitation programs have been developed using the Microsoft Kinect sensor [38][39][40][41] and the Nintendo Wii board [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%